Keyhole hysterectomy is effective for women with heavy menstrual bleeding. (3rd January 2020) - Cook, Rob; Lyon-Maris, Johnny; Davidson, Peter
The study: Cooper K, Breeman S, Scott NW, et al. Laparoscopic supracervical hysterectomy versus endometrial ablation for women with heavy menstrual bleeding (HEALTH): a parallel-group, open-label, randomised controlled trial. Lancet 2019;394:1425-36. The study was funded by the NIHR Health Technology Assessment Programme (project number 12/35/23). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000837/keyhole-hysterectomy-is-effective-for-women-with-heavy-menstrual-bleeding